Disbarracking Tumbes… valorization of military heritage from the perspective of its urban-social context: The case of the “General Coloma barracks” (Peru) - La Rosa Ramos, Jean (2026)
The valorization of military heritage in Peru still covers very little of what was built during the modern era, a period in which an important process of strengthening the country's barracks infrastructure took place. Tumbes, as a coastal and border territory, has a close relationship with the Peruvian Army, however, the decrease in activities and functions has led to this bond being lost over time, though it remains present in the city through its built heritage. The General Coloma Barracks is one of the oldest in the city of Tumbes and is at risk of being destroyed. This qualitative and exploratory research analyzes the formal, functional, and symbolic values associated with the barracks, its relationship with its urban-social context, as well as the influence it has had on it. The findings highlight its formal and symbolic value, mainly associated with the history and identity of the city, in order to contribute to its categorization as heritage.